Meeting `Human Needs Toward a New Public Philosophy - Meyer, Jack A.; American Enterprise Institute for Public Policy Research (Washington; London: American Enterprise Institute for Public Policy Research, 1982)
This book spans diverse disciplines and philosophies. The AEI have examined the historical and philosophical tradition of private sector initiatives; identified numerous options for the private sector and for public/private partnerships; highlighted examples of creative and effective local leadership in dealing with social problems; and pointed out nagging administrative and regulatory barriers that stand in the way of privately initiated social programs
Includes bibliographical references.
ne 17/05/2018
Loans
Keywords: Industries; Labor unions; Associations, institutions, etc